Spiritual formation as the hero's journey in John of Ruusbroec - Pelfrey, Robert (Robert C.), author.
1 online resource
Keywords: "This book examines the theology of spiritual formation developed by fourteenth-century Flemish mystic John of Ruusbroec, arguing that his formational path clearly and consistently displays the characteristics of the archetypal narrative structure of the hero's journey. To start with a hermeneutical dialogue between scholars of the hero's journey and Ruusbroec is established, employing the work of Hans-Georg Gadamer. The author then examines the stages and tropes of the hero's journey according to Vladimir Propp, Joseph Campbell, Northrop Frye, René Girard, Dean Miller, and others, exploring the parallels in Ruusbroec's writing and theology of spiritual formation. The book follows Ruusbroec's story of answering the divine call, journeying inward and experiencing the trials of spiritual transformation, attaining the treasure of divine union, and returning in loving service to others. Finally, the ramifications of the argument for the interpretation and application of other mystical and heroic narratives are considered. Offering a new perspective on John of Ruusbroec, mystical theology, and the hero's journey as spiritual quest, this volume will be of interest to scholars of mysticism, theology, formative spirituality, narrative theory, and religious literature of the Low Countries"--